2023
DOI: 10.9734/ajbgmb/2023/v14i4319
|View full text |Cite
|
Sign up to set email alerts
|

An Environmentally Safe Production of Xylanases by Fusarium sp. EA 1.3.1 Using Agroindustrial Residues: Biochemical Characterization and Potential Applications

Abstract: Renewable energy-related biotechnologies such as biofuels produced from low-cost residual sources that represent clean technologies have become a partial solution to environmental problems. We sought to optimize the cultivation parameters of the fungus Fusarium sp. EA1.3.1 and biochemically characterize the naturally produced xylanases from the fungus. The development of the fungus was analyzed considering the variations in the resources available and by biochemical analysis of the crude extract. The compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Fusarium solani is a candidate for the production of extracellular xylanases. There have been few reports on the efficient production of xylanases and exploratory studies about its xylanolytic activity [14] and optimization of enzyme production [15,16]. In a previous study, Fusarium solani was isolated from bean crops, identified, and selected from a group of one hundred and three fungal isolates for its notable ability to produce extracellular xylanases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium solani is a candidate for the production of extracellular xylanases. There have been few reports on the efficient production of xylanases and exploratory studies about its xylanolytic activity [14] and optimization of enzyme production [15,16]. In a previous study, Fusarium solani was isolated from bean crops, identified, and selected from a group of one hundred and three fungal isolates for its notable ability to produce extracellular xylanases [17].…”
Section: Introductionmentioning
confidence: 99%